2022
DOI: 10.1039/d2qo00241h
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of aryl-H-phosphinates applied in the synthesis of P-stereogenic compounds including a Brønsted acid NMR solvating agent

Abstract: A library of racemic H-phosphinates incorporating a variety of alkoxy groups or substituted aryl groups was prepared. Starting with a resolving agent screening, an efficient enantioseparation method was developed and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 86 publications
1
6
0
Order By: Relevance
“…However, the crystals were a non-centrosymmetric twin, and the ( S ) absolute configuration of the P -stereogenic center was established during the measurement ( Figure 1 ). In this manner, the (−) sign of optical rotation could be linked to an ( S ) absolute P -configuration for ( S )-1-adamantyl phenylphosphonothioic acid (( S )- 2a ), whose correlation was postulated in our previous paper [ 25 ] on the basis of the literature analogy [ 21 ]. The absolute configurations of the ( S )-1-adamantyl (4-methoxyphenyl)phosphonothioic acid (( S )- 2b ) and ( S )-1-adamantyl (4-trifluoromethyphenyl)phosphonothioic acid (( S )- 2c ) could not be verified by XRD measurements, but an ( S ) absolute configuration was assigned to the (−) sign of optical rotation on the basis of structural similarity with compound ( S )- 2a .…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…However, the crystals were a non-centrosymmetric twin, and the ( S ) absolute configuration of the P -stereogenic center was established during the measurement ( Figure 1 ). In this manner, the (−) sign of optical rotation could be linked to an ( S ) absolute P -configuration for ( S )-1-adamantyl phenylphosphonothioic acid (( S )- 2a ), whose correlation was postulated in our previous paper [ 25 ] on the basis of the literature analogy [ 21 ]. The absolute configurations of the ( S )-1-adamantyl (4-methoxyphenyl)phosphonothioic acid (( S )- 2b ) and ( S )-1-adamantyl (4-trifluoromethyphenyl)phosphonothioic acid (( S )- 2c ) could not be verified by XRD measurements, but an ( S ) absolute configuration was assigned to the (−) sign of optical rotation on the basis of structural similarity with compound ( S )- 2a .…”
Section: Resultsmentioning
confidence: 84%
“…The 1-adamantyl aryl- H -phosphinates ( 1 ) were synthesized according to a literature procedure [ 24 ]. In our previous paper [ 25 ], the synthesis of 1-adamantyl phenylthiophosphonic acid ( 2a ) was reported by reacting 1-adamantyl phenyl- H -phosphinate ( 1a ) with elemental sulfur at room temperature in the presence of triethylamine. However, it was found that the reaction is faster, and the purification is more efficient, when the H -phosphinates ( 1 ) are refluxed in THF with elemental sulfur without any base, and the crude thiophosphonate ( 2 ) is purified as a diethylamine salt ( 2 ꞏEt 2 NH), which is followed by an acidic liberation step [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations